Green light for chloroplast outer-membrane proteins. - Bédard, J; Jarvis, P (2008)
Most chloroplast proteins are encoded in the cell nucleus, translated in the cytosol, and targeted to the organelle in a post-translational manner. Our understanding of how proteins are targeted to the outer envelope membrane of chloroplasts has been improved with the identification of a specific soluble sorting factor.